2018
DOI: 10.3389/fonc.2018.00620
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Long-Term Outcomes in Patients With Colorectal Cancer

Abstract: Background: The association between body mass index (BMI) and colorectal cancer is unique. There are several patient- and tumor-related factors that affect this and associations are not entirely clear. The primary aim of this study is to examine the association between BMI and survival after colorectal cancer diagnosis.Methods: Among 26,908 Mayo Clinic patients diagnosed with colorectal cancer between 1972 and 2017, 3,799 patients had information on BMI within 6 months prior to cancer diagnosis. Multivariable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 26 publications
4
49
1
Order By: Relevance
“…In response to endocrine and metabolic signals, adipose tissue releases innumerable hormones such as leptin, adiponectin and resistin, in addition to cytokines such as TNFα, which promote a state of chronic inflammation and insulin resistance, a condition associated with increased IGF-1 synthesis, the carcinogenic potential for increased cell proliferation [33] [34]. The high prevalence of overweight individuals was associated with an increased risk for CRC, corroborating the findings of an investigation conducted in Arizona-USA [35] and Australia [36], in which patients with CRC were evaluated and overweight was diagnosed in more than 68% of the individuals, with a higher prevalence among males.…”
Section: Resultssupporting
confidence: 74%
“…In response to endocrine and metabolic signals, adipose tissue releases innumerable hormones such as leptin, adiponectin and resistin, in addition to cytokines such as TNFα, which promote a state of chronic inflammation and insulin resistance, a condition associated with increased IGF-1 synthesis, the carcinogenic potential for increased cell proliferation [33] [34]. The high prevalence of overweight individuals was associated with an increased risk for CRC, corroborating the findings of an investigation conducted in Arizona-USA [35] and Australia [36], in which patients with CRC were evaluated and overweight was diagnosed in more than 68% of the individuals, with a higher prevalence among males.…”
Section: Resultssupporting
confidence: 74%
“…This may explain the observed mortality advantage among the overweight surgical population. Another study done on 26,908 Mayo Clinic colorectal cancer patients demonstrated a significant disadvantage in overall survival amongst underweight patients as compared to both the normal and overweight patient groups [22]. We believe that it is underweight patients at risk of malnutrition who have a significant survival disadvantage rather than a high BMI actually being protective.…”
Section: Body Mass Index (Bmi)mentioning
confidence: 72%
“…The associations between weight, body mass index (BMI), and survival outcomes have previously been shown in other studies [33][34][35][36]. A meta-analysis that examined almost 100 studies involving >2.88 million patients confirmed that being overweight (BMI 25-30 kg/m 2 ) was associated with a lower risk of all-cause mortality [33].…”
Section: Discussionmentioning
confidence: 68%